Effects of Euthanasia on Animal Research - Maharani, Ni Putu Radela; Fadlyah, Nur Ashfiya; Setyaningrum, Dyah Ayu Woro; Hairunisa, Nany (Faculty of Veterinary Medicine Universitas Brawijaya, 2024)
The use of experimental animals is widely conducted in the medical field, both for research on the processes of disease occurrence (pathogenesis), the causes of disease (etiology), and research on therapy. Therefore, it is important to understand how euthanasia in experimental animals affects the integrity of the sample and its influence on research results. This article was compiled from several literature sources searched from Google Schoolar and PubMed published within the last 10 years, with keywords such as